The Limits of Expectations and the Minimization of Collateral Consequences: The Experience of Electronic Home Monitoring. (9th May 2020) - Kirk, Gabriela
Abstract: Electronic home monitoring (EHM), also known as house arrest, is often described by policy makers as a less punitive, more humane alternative to incarceration. However, studies on its use have found it is often not used as an alternative, but rather as an increase in the level of supervision for individuals in the criminal justice system. This fact calls into question whether the language of alternatives and direct comparisons to incarceration obscures our understanding of both the sanction and how individuals experience it. Although previous studies of the experience of EHM have concluded that individuals do not find the sanction overly burdensome, this article articulates the importance of considering 1) how respondents frame their experience on EHM in comparison to incarceration and 2) how they draw on expectations surrounding their legal alternatives. Using 30 interviews with individuals who have been on EHM in Chicago, Illinois, I argue that the pervasiveness of the prison distorts expectations of the legal process and causes respondents to minimize the hardships they detail. Both the existing framing of studies on EHM and the ways in which individuals experience it demonstrate the hegemony of carceral logics in an era of mass incarceration.